Getting the Most Out of Public Sector Decentralisation in Mexico - Joumard, Isabelle (OECD Economics Department Working Papers, 2005)
Enhanced autonomy of sub-national governments has spurred innovative management. Spending assignments across levels of government, however, often overlap and/or are not yet fully understood by most citizens. Sub-national governments' accountability is further reduced by the heavy reliance on federal transfers, as opposed to own-revenues (taxes and user fees). In addition, the use of federal transfers as collateral for states' borrowing potentially undermines the role of financial markets in disciplining fiscal behaviour. Getting the most out of decentralisation would thus require a national agreement clarifying responsibilities for each level of government. Improving sub-national governments' incentives in delivering cost-effective public services would further require improving the quality of information on actual spending and outcomes, raising the volume of their own taxes and reforming the grant systems. Decentralisation should also be more consistent with the aim of improving interregional equity in obtaining access to core public services. This Working Paper relates to the 2005 OECD Economic Survey of Mexico (www.oecd.org/eco/surveys/mexico)